On the naturalness of touchless: putting the "interaction" back into NUI - O'Hara, Kenton; Harper, Richard; Mentis, Helena; Sellen, Abigail; Taylor, Alex (ACM Transactions on Computer-Human Interaction, 2013)
After many decades of research, the ability to interact with technology through touchless gestures and sensed body movements is becoming an everyday reality. The emergence of Microsoft Kinect, among a host of other related technologies, has had a profound effect on the collective imagination, inspiring and creating new interaction paradigms beyond traditional input mechanisms such as mouse and keyboard. Kinect and other technologies form part of the broader suite of innovations that have come to be characterised as Natural User Interfaces (NUI) (e.g. Widgor and Wixon, 2011, Norman, 2011). This moniker includes not only the vision techniques that form that basis of Kinect, but also natural language interfaces, pen-based input and multi touch gestural input, amongst other techniques. The excitement around touchless and body-based interfaces has been accompanied by an increasingly powerful narrative, one that makes the eponymous claim that these new technologies offer an intuitive interface modality, one that does not require users to develop specialist techniques for communicating to computers.